2014
DOI: 10.1111/jgs.12622
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in Daytime Sleeping Is Associated with Improvement in Cognition After Hospital Discharge in Older Adults

Abstract: Background/Objectives: The longitudinal association between sleep and cognitive functioning is not well understood in late-life. Examination of the association between a potentially modifiable risk factor such as sleep, and cognitive change in at-risk older adults is of both theoretical and practical importance. We examined the relationship between changes in objectively-assessed sleep and global cognitive functioning from inpatient post-acute rehabilitation to 6-months follow-up. Design: Secondary analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 35 publications
2
25
0
Order By: Relevance
“…Still other researchers observed relationships between long sleep duration, but not short sleep duration, and general cognitive functioning (Faubel et al, 2009 ). Beyond our recent work demonstrating that when sleep improves following hospital discharge, so too does cognitive functioning (Dzierzewski et al, 2014 ), there is a dearth of research examining the relationship between sleep and cognitive functioning in hospitalized older adults. Such research is important, given the increased risk for negative cognitive changes associated with hospitalization in late-life (Wilson et al, 2012 ) and the relative ease of assessing self-reported sleep duration.…”
Section: Introductionmentioning
confidence: 96%
“…Still other researchers observed relationships between long sleep duration, but not short sleep duration, and general cognitive functioning (Faubel et al, 2009 ). Beyond our recent work demonstrating that when sleep improves following hospital discharge, so too does cognitive functioning (Dzierzewski et al, 2014 ), there is a dearth of research examining the relationship between sleep and cognitive functioning in hospitalized older adults. Such research is important, given the increased risk for negative cognitive changes associated with hospitalization in late-life (Wilson et al, 2012 ) and the relative ease of assessing self-reported sleep duration.…”
Section: Introductionmentioning
confidence: 96%
“…and decreased cognitive functioning following discharge. [12][13][14] While these fi ndings suggest that disturbed sleep represents an important independent risk factor for poor outcomes among older adults recovering from acute health events and hospitalizations, questions remain concerning (1) how sleep quality may change throughout the course of an acute health event and/ or hospitalization, and (2) the optimal methods to assess sleep disturbances in older adults during this process so interventions can be effectively targeted.…”
mentioning
confidence: 99%
“…4,5 In addition, long-term changes in health status, pain symptoms, and cognitive impairment are factors with known negative associations with sleep disturbances in older adults. [6][7][8][9][10][11][12] This paper aims to extend previous work and examine patterns and predictors of sleep quality throughout the hospitalization process (i.e., from pre-admission through 1 year post-discharge follow-up).…”
mentioning
confidence: 99%
“…Disrupted sleep, characterized by shorter sleep duration during the night and greater daytime sleepiness has been related to reduced physical and cognitive performance (Goldman et al, 2007). Sleep itself and decreased daytime sleeping may however improve motor consolidation after physical training (Siengsukon & Boyd, 2009) and the cognitive function after discharge (Dzierzewski et al, 2014). Prevention of sleep disturbances and improvement in sleep quality may therefore be necessary to achieve optimal rehabilitation outcome after stroke.…”
Section: Introductionmentioning
confidence: 99%